Hypermethylation of the Promoter Region of miR-23 Enhances the Metastasis and Proliferation of Multiple Myeloma Cells via the Aberrant Expression of uPA - Ran, Qijie; Xu, Dehong; Wang, Qi; Wang, Dongsheng (Frontiers in Oncology, 2022)
Multiple myeloma has a long course, with no obvious symptoms in the early stages. However, advanced stages are characterized by injury to the bone system and represent a severe threat to human health. The results of the present work indicate that the hypermethylation of miR-23 promoter mediates the aberrant expression of uPA/PLAU (urokinase plasminogen activator, uPA) in multiple myeloma cells. miR-23, a microRNA that potentially targets uPA’s 3’UTR, was predicted by the online tool miRDB. The endogenous expressions of uPA and miR-23 are related to disease severity in human patients, and the expression of miR-23 is negatively related to uPA expression. The hypermethylation of the promoter region of miR-23 is a promising mechanism to explain the low level of miR-23 or aberrant uPA expression associated with disease severity. Overexpression of miR-23 inhibited the expression of uPA by targeting the 3’UTR of uPA, not only in MM cell lines, but also in patient-derived cell lines. Overexpression of miR-23 also inhibited in vitro and in vivo invasion of MM cells in a nude mouse model. The results therefore extend our knowledge about uPA in MM and may assist in the development of more effective therapeutic strategies for MM treatment.